Three-dimensional hydrodynamical CO5BOLD model atmospheres of red giant stars: V. oxygen abundance in the metal-poor giant HD 122563 from OH UV lines - Prakapavičius, Dainius; Ludwig, Hans-Günter (Arxiv, 2016)
Although oxygen is an important tracer of the early Galactic evolution, its abundance trends with metallicity are still relatively poorly known at [Fe/H] < -2.5. This is in part due to a lack of reliable oxygen abundance indicators in the metal-poor stars, in part due to shortcomings in 1D LTE abundance analyses. In this study we determined the oxygen abundance in the metal-poor halo giant HD 122563 using a 3D hydrodynamical CO5BOLD model atmosphere. Our main goal was to understand whether a 3D LTE analysis may help to improve the reliability of oxygen abundances determined from OH UV lines in comparison to those obtained using standard 1D LTE methodology. The oxygen abundance in HD 122563 was determined using 71 OH UV lines located in the wavelength range between 308-330 nm. The analysis was done using a high-resolution VLT UVES spectrum with a 1D LTE spectral line synthesis performed using the SYNTHE package and classical ATLAS9 model atmosphere. Subsequently, a 3D hydrodynamical CO5BOLD, and 1D hydrostatic LHD model atmospheres were used in order to compute 3D-1D abundance corrections. For this, the microturbulence velocity used with the 1D LHD model atmosphere was derived from the hydrodynamical CO5BOLD model atmosphere. As in previous studies, we found trends of the 1D LTE oxygen abundances determined from OH UV lines with line parameters, such as the line excitation potential and the line strength. These trends become significantly less pronounced in 3D LTE. Using OH UV lines we determined a 3D LTE oxygen abundance in HD 122563 of A(O) = 6.23 +/- 0.13. This is in fair agreement with the oxygen abundance obtained from OH IR lines, A(O) = 6.39 +/- 0.11, but it is noticeably lower than that determined using the forbidden [OI] line, A(O) = 6.53 +/- 0.15. While the exact cause for this discrepancy remains unclear, it is very likely that non-LTE effects may play a decisive role here.